2014
DOI: 10.1016/j.neuron.2013.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Increased L1 Retrotransposition in the Neuronal Genome in Schizophrenia

Abstract: Recent studies indicate that long interspersed nuclear element-1 (L1) are mobilized in the genome of human neural progenitor cells and enhanced in Rett syndrome and ataxia telangiectasia. However, whether aberrant L1 retrotransposition occurs in mental disorders is unknown. Here, we report high L1 copy number in schizophrenia. Increased L1 was demonstrated in neurons from prefrontal cortex of patients and in induced pluripotent stem (iPS) cell-derived neurons containing 22q11 deletions. Whole-genome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
288
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(295 citation statements)
references
References 40 publications
6
288
0
1
Order By: Relevance
“…Finally, transposition has both beneficial and deleterious effects on human health (47). As opposed to its proposed role in homeostatic mechanism to environmental stress and adaptive behavior (48), increased LINE1 copy number has been found to be associated with Rett syndrome and schizophrenia (5,49). Furthermore, depletion of the stress-granule component, transposon-binding protein, TAR DNA-binding protein 43, leads to neurodegeneration in the familial form of amyotrophic lateral sclerosis and frontotemporal dementia (7).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, transposition has both beneficial and deleterious effects on human health (47). As opposed to its proposed role in homeostatic mechanism to environmental stress and adaptive behavior (48), increased LINE1 copy number has been found to be associated with Rett syndrome and schizophrenia (5,49). Furthermore, depletion of the stress-granule component, transposon-binding protein, TAR DNA-binding protein 43, leads to neurodegeneration in the familial form of amyotrophic lateral sclerosis and frontotemporal dementia (7).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous such events could be detected in tumor tissues and cells (Miki et al 1992;Lee et al 2012), some of which might be causal. Somatic integration even was proposed to contribute to neuropsychiatric disease, such as schizophrenia (Bundo et al 2014). Apart from being detrimental or neutral, a minority of events has the potential to turn out beneficial.…”
Section: Te Functions: To the Moon!mentioning
confidence: 99%
“…To study chronological changes in the L1-ORF2 copy numbers, 6 groups of mice at various ages (3,8,15,18,20, and »55 weeks) were analyzed. Six mice from each group (3 males and 3 females) and 6 8-week-old mice used for validation (3 males and 3 females) were deeply anaesthetised and perfused transcardially with cold 4% paraformaldehyde in phosphate-buffered saline (PBS), and genomic DNA was extracted from the right and left hippocampi and the prefrontal cortex.…”
Section: Animalsmentioning
confidence: 99%
“…2 Notably, L1 is active in neuronal precursor cells, and L1-RTP insertions provoke the expression of neuron-specific genes when their gene structures are altered by de novo L1 insertion. [3][4][5] Recent studies have identified L1-mediated somatic mosaicism in normal adult brains, 6,7 and high copy numbers of L1 were detected in the brain of a schizophrenia patient, 8 Okudaira et al recently reported that stimulants such as methamphetamine and cocaine induced L1-RTP in neuronal cells, 9,10 and Moszczynska et al demonstrated that glutamate activated L1-RTP. 10 These observations imply that L1-RTP is physiologically regulated via the axis of glutamate and the glutamate receptor and that normal brain maturation is affected by the deregulation of L1-RTP, which functions as a molecular basis of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%